Wildfire Effects on Soils of a 55‐Year‐Old Chaparral and Pine Biosequence. Issue 2 (8th April 2016) - Graham, Robert C.; Egerton-Warburton, Louise M.; Hendrix, Paul F.; Shouse, Peter J.; Johnson-Maynard, Jodi L.; Quideau, Sylvie A.; Sternberg, Paul D.; Jobes, Jack A.; Breiner, Joan M.
Abstract : Core Ideas: Native chaparral and pine plots were studied before and after a wildfire. Macrofaunal pores kept infiltration rates high, minimizing post‐fire runoff. Loss of cover and plant transpiration made the post‐fire soil warmer and moister. The soil chemical and biological environments were extensively altered by fire. Original plant species re‐emerged and soils neared pre‐fire conditions after 6 mo. A chaparral and pine biosequence established in 1946 was burned in a wildfire in 2002. Thorough studies of the soil environments during the previous two decades established a baseline for comparison of post‐fire changes. Aboveground vegetation was reduced to charred stems, and litter layers were combusted to white ash and charred material. Nevertheless, during the first year after the fire, runoff and erosion were minimal because biotically produced macropores maintained high infiltration rates. Loss of cover and plant transpiration made the soil warmer and moister. Combustion of organic matter mineralized constituent cations, increasing base cation concentrations in soil solutions and solid phases within the first few months after the fire. The pH, C, and N also increased in the soil, and the biological environment was extensively altered. Surface‐active macrofauna increased, though seasonal patterns of abundance were unchanged. Post‐fire fungal communities were distinctly different from pre‐fire communities and were more similar to each other than were pre‐fire communities. Overall, many of the wildfire impacts appear to be of short duration. Within 6 mo, original species were resprouting or emerging as seedlings, and most soil chemical, physical, and biological properties were either similar to pre‐fire conditions or were rapidly returning toward them.